NILAI TAMBAH SUMBER DAYA LOKAL SEBAGAI PRODUK UNGGULAN PADA KELOMPOK PEKARANGAN PANGAN LESTARI (P2L) EDELWEIS - Praptiningsih Gamawati Adinurani; Ratna Mustika Wardhani (JURNAL DAYA-MAS, 2023)
Sustainable Food Yard (P2L) activities utilize a sustainable agricultural approach, utilization of local resources, community empowerment, and marketing orientation. The Edelweiss P2L group in Pilangbango Village, Kartoharjo District, Madiun City, consists of homemakers who have yards but need basic knowledge of good farming and utilization of crop yields. Community service activities aim to turn the results of the P2L program into value-added products. The dedication method is carried out through discussion, counseling, and mentoring of program activities. The results of the implementation of the program show that the activities are carried out correctly. Discussion activities, program evaluation, counseling, and mentoring can increase the knowledge and skills of members in utilizing their yards by cultivating intensively, especially chilies, tomatoes, eggplants, mustard greens, Brazilian spinach, and kale. Yields can meet family nutritional adequacy and increase income. Eggplant, mustard greens, and Brazilian spinach commodities are prioritized as superior products with marketing in processed forms such as mustard greens noodles, mustard sticks, eggplant brownies, and Brazilian spinach roulade.